Synthesis, spectroscopic and X-ray crystallographic analysis of N-(2-(2-(4-chlorophenoxy)acetamido)phenyl)-1H-indole-2-carboxamide - Al-Ostoot, Fares Hezam; Stondus, Jigmat; Anthal, Sumati; Venkatesh, Geetha Doddenahally; Mohammed, Yasser Hussein Eissa; Sridhar, Mandayam Anandalwar; Khanum, Shaukath Ara; Kant, Rajni (European Journal of Chemistry, 2019)
Medicinal chemistry of indole analogs constitutes important therapeutic agents with anti-oxidant, anti-HIV and anti-cancer activities. Indole nucleus is frequently found in synthetic and natural products, pharmaceuticals, functional materials, agrochemicals, etc. The title compound, N-(2-(2-(4-chlorophenoxy)acetamido)phenyl)-1H-indole-2-carboxamide (5), has been synthesized in good yield by stirring the compound N-(2-aminophenyl)-2-(4-chlorophenoxy)acetamide (3) with 1H-indole-2-carboxylic acid (4), in dry dichloromethane followed by the addition of 2,6-lutidine, and o-(benzotriazol-1-yl)-N,N,N',N'-tetramethyl uraniumtetrafluoroborate in cooled condition. Compound 5 was synthesized and characterized by the conventional spectroscopic techniques (1H NMR, 13C NMR and LC-MS) and the three-dimensional structure was elucidated by using single crystal X-ray diffraction methods. It crystallizes in the monoclinic crystal system with space group P21/c. The structure was solved by direct methods and refined by full matrix least square procedure to a final R value of 0.043 for 2490 observed reflections. Three intra-molecular interactions of the type N-H···N and C-H···N were observed. The packing of molecules in the unit cell is governed by N-H···O and C-H···O intermolecular H-boned interactions which leads to the formation of infinite staking chain along [001] direction. In addition, two weak C-H···π interactions also contribute to molecular packing.